ChemInform Abstract: Synthesis and Biological Activity of 10‐Aza‐narciclasine. Issue 22 (15th May 2015) - Vshyvenko, Sergey; W'Giorgis, Zemane; Weber, Audrey; Neverova, Natalia; Hedberg, Bradley; Hudlicky, Tomas
Abstract: Title compound (VI) is synthesized starting from pyridine derivative (I) over 12 steps in an overall yield of 2.05%.